Procrastination and Academic Self-efficacy in University Students from Lima - Burgos-Torre, Kattya S. (2020)
This research is cross-sectional study with correlational design (Hernández-Sampieri & Mendoza, 2018). The objective is to relate procrastination and self-efficacy in the academic context.178 university studentsparticipated, who were administered the Academic Procrastination Scale (EPA, Dominguez, Villegas & Centeno, 2014) and the Perceived Self-Efficacy Scale for Academic Situations (EAPESA, Dominguez, Villegas, Yauri, Mattos & Ramírez, 2012). It was found that the variables are correlated, the academic self-regulation correlates positively with academic self-efficacy(.39); specifically, the postponement of activities dimensionnegativelycorrelates with self-efficacy (-.23),It was also found that there are differences in the two variables when comparing the three groups of students by semesters, the students of intermediate semesters presenthigher levels of postponement ofactivities thanthose who star studies and those how finish studies, also it was found there are differences between gender;women have higher levels of academic self-regulation.